2018
DOI: 10.1097/pec.0000000000001580
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Severe Clinical Course in Children With Carbon Monoxide Poisoning

Abstract: Objective Carbon monoxide (CO) is a gas, which is produced by incomplete combustion of hydrocarbon-containing substances, and causes significant tissue and organ damage in the common event of CO poisoning. This study aims to evaluate the demographic, clinical, and laboratory characteristics of patients diagnosed with CO poisoning in the emergency department and to determine the factors associated with severe course in the acute phase of poisoning. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
0
11
1
Order By: Relevance
“…Han et al reported that NLR was predictive for myocardial injury in patients with CO poisoning [ 37 ]. In a study by Akcan Yildiz in pediatric patients with CO poisoning, it was reported that a high leukocyte count was useful in predicting prognosis and directing treatment [ 38 ]. In a study by Moon et al with adults with CO poisoning, it was shown that both admission neutrophil count and NLR were predictive of troponin-I elevation when used together with clinical parameters in patients without troponin-I elevation or ischemic ECG changes at admission [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Han et al reported that NLR was predictive for myocardial injury in patients with CO poisoning [ 37 ]. In a study by Akcan Yildiz in pediatric patients with CO poisoning, it was reported that a high leukocyte count was useful in predicting prognosis and directing treatment [ 38 ]. In a study by Moon et al with adults with CO poisoning, it was shown that both admission neutrophil count and NLR were predictive of troponin-I elevation when used together with clinical parameters in patients without troponin-I elevation or ischemic ECG changes at admission [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These negative results are contrasted by a recently published, large retrospective cohort analysis, which showed reduced fatality after HBOT especially in patients younger than 20 years (34) (Table 3). In parallel to adults, children (0-18 years, median 11 years) with severe CO poisoning also had raised troponin T concentrations (39).…”
Section: Boxmentioning
confidence: 98%
“…These factors include advanced age, prolonged CO exposure, high carboxyhemoglobin levels, altered mental status upon presentation, prolonged coma, delayed time to treatment, metabolic acidosis, elevated lactate levels, myocardial injury with high troponin T levels, and early brain computed tomography findings (such as globus pallidus or white matter lesions). In additionally, Glasgow Coma Scale score, Poison Severity Score, CO-modified Poison Severity Score, and Sequential Organ Failure Assessment score have been identified as important predictors of COP prognosis 2–6 …”
mentioning
confidence: 99%
“…In additionally, Glasgow Coma Scale score, Poison Severity Score, CO-modified Poison Severity Score, and Sequential Organ Failure Assessment score have been identified as important predictors of COP prognosis. [2][3][4][5][6] To obtain a comprehensive evaluation of a patient's overall status and prognosis in cases of COP, it is crucial to consider multiple inflammatory biomarkers and clinical variables, as well as incorporate a comprehensive risk stratification score. Although the study by Guven et al adds to our understanding of the potential role of MPV and RDW in predicting COP severity, relying solely on these markers may not provide sufficient information to accurately predict patient outcomes and guide treatment decisions, particularly in cases where hyperbaric oxygen therapy is needed.…”
mentioning
confidence: 99%